Reduction of time-to-market as a source of competitive advantage : the case of industrial products - Nunes, Manuel L. (2007)
In the present study, a number of techniques and methodologies which help reducing new products time-to-market were identified. Based on a sample of 32 companies belonging to the industry car components in Portugal, an analysis was made of the relationship between these techniques and methodologies and the time-to- market, and between former and the success of new components in the market. According to the statistic analysis made, there is a direct relationship between the success of new products and the use of some techniques of manufacture/industrialization, information and design technologies. The analysis made also indicates the existence of other determining factors in the success of new products, such as the reduction of new product time-to-market and the participation of marketing and production departments, engineers and designers, clients and suppliers in process of conception and development of new products.